Factors of Service Quality and Price Perception Affecting on The Loyalty of Entrepreneurs in a Large Flea Market, Chon Buri Province - Saensak, Thanathip; Saraphat, Somboon (Journal of Applied Economics and Management Strategy, 2025)
The objectives of this research are: 1) to study the level of service quality, the level of price perception, and the level of loyalty of entrepreneurs in a large flea market in Chonburi Province; and 2) to study the influence of service quality and price perception on the loyalty towards the provider of space rental services in a large flea market in Chonburi Province. This research aims to enhance service quality in flea markets, enabling vendors to consistently lease spaces and maintain long-term tenancy. The goal is to support the market's sustainable operation and its ability to address the issue of unstable income, which may arise from economic downturns. The sample used in the study consisted of 340 entrepreneurs from a large flea market in Chonburi Province. The statistical methods used for data analysis included descriptive statistics, frequency distribution, percentage, mean, standard deviation, and multiple regression analysis. The results of the research are as follows: 1) Retail entrepreneurs exhibit the highest level of agreement regarding overall service quality, a high level of price perception and the highest level of agreement regarding loyalty. 2) Service quality and price perception factors significantly influence the four dimensions of loyalty among entrepreneurs in a large flea market in Chonburi Province at the 0.05 significance level. The researcher believes that the findings of this study will be beneficial to both flea market operators and vendors, as they can utilize the information gained from this research to develop and improve the market. This will contribute to the sustainable operation of the business. For example, it may involve training to maintain the standard of market management staff, increasing communication through congenial greetings and providing clear, useful advice to vendors, as well as addressing issues in a timely manner once reported by the vendors.